je - nous. - Musée d'Ixelles, Ixelles (Ixelles : Musée d'Ixelles, 1975)
Anatol ; Andre, Carl ; Artschwager, Richard ; Balderi, I. ; Ben ; Beuys, Joseph ; Boltanski, Christian ; Brecht, George ; Buren, Daniel ; etc.
je - nous : ik - wij, Musée d'Ixelles, 23.5 - 13.7.1975
kunstcatalogus